Antioxidant activities of fucoidan degraded by gamma irradiation and acidic hydrolysis. (April 2015) - Lim, Sangyong; Choi, Jong-il; Park, Hyun
Abstract: Low molecular weight fucoidan, prepared by radical degradation using gamma ray was investigated for its antioxidant activities with different assay methods. As the molecular weight of fucoidan decreased with a higher absorbed dose, ferric-reducing antioxidant power values increased, but β -carotene bleaching inhibition did not change significantly. The antioxidant activity of acid-degraded fucoidan was also examined to investigate the effect of different degradation methods. At the same molecular weight, fucoidan degraded by gamma irradiation showed higher 1, 1-diphenyl-2-picrylhydrazyl radical scavenging activity than that observed with the acidic method. This result reveals that in addition to molecular weight, the degradation method affects the antioxidant activity of fucoidan. Highlights: Antioxidant activity of fucoidan degraded by gamma-irradiation was analyzed. Degree of change of antioxidant activity was dependent on the measuring method. Acid hydrolyzed fucoidan was compared to gamma-irradiated for its antioxidant activity.